2008
DOI: 10.1089/end.2007.0114
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Double-Pigtail Stent in Patients with Upper Urinary Tract Diseases: Report of 2685 Cases

Abstract: DPS is a safe and useful adjunct for both endoscopic and open procedures to treat upper urinary tract diseases. Most of the complications of DPS placement can be well managed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 26 publications
2
50
1
3
Order By: Relevance
“…This study showed that DJ stent insertion has increased the frequency, flank pain and suprapubic pain to 40, 33.33 and 20%, respectively. This is in agreement with previous meta-analysis wherein frequency, urgency and suprapubic pain has been shown to be 50 -60%, 57 -60% and 30%, respectively 7,13 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study showed that DJ stent insertion has increased the frequency, flank pain and suprapubic pain to 40, 33.33 and 20%, respectively. This is in agreement with previous meta-analysis wherein frequency, urgency and suprapubic pain has been shown to be 50 -60%, 57 -60% and 30%, respectively 7,13 .…”
Section: Discussionsupporting
confidence: 93%
“…This is lower than what had been observed previously, i.e. 57 -60% and 25% of cases experienced urgency and hematuria, respectively 6,7 . The discrepancy might be due to limited number of cases in the present study (60) compared with >1,500 cases in those study 6,7 .…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Hao P et al [12] evaluated 2685 cases of DJ stent for different nephroureteric conditions and concluded that these stents are a safe and useful adjunct for both endoscopic and open procedures, if it was kept in situ for less than 28 days.…”
Section: Introductionmentioning
confidence: 99%